Proton‐Radiation Tolerant All‐Perovskite Multijunction Solar Cells (Adv. Energy Mater. 41/2021). Issue 41 (4th November 2021) - Lang, Felix; Eperon, Giles E.; Frohna, Kyle; Tennyson, Elizabeth M.; Al‐Ashouri, Amran; Kourkafas, Georgios; Bundesmann, Jürgen; Denker, Andrea; West, Kevin G.; Hirst, Louise C.; Neitzert, Heinz‐Christoph; Stranks, Samuel D.
Abstract : Photovoltaics In article number 2102246 Felix Lang, Giles E. Eperon, Samuel D. Stranks and co‐workers investigate efficient all perovskite‐based tandem photovoltaics. This class of photovoltaics combine high specific power with good tolerance to the harsh radiation environment in space, thereby promising a next‐generation of lightweight and cost‐efficient solutions to power private space exploration, low‐cost missions as well as future habitats on the Moon and Mars.